Evolution of a Neoproterozoic suture in the Iberian Massif, Central Portugal: igneous and metamorphic events at the Ossa Morena Zone/Central Iberian Zone boundary - Neiva, A.M.R. (2021)
ABSTRACT: The existence of the late Neoproterozoic supercontinent Pannotia (ca. 650-540 Ma) is controversial. Several proxies for supercontinent assembly and break-up have been recognized. Global orogeny and granitoid magmatism, detrital zircon and monazite age peaks and extreme conditions of metamorphism are some of the proxies pointed out for supercontinent assembly. The amalgamation of Pannotia was accompanied by the Pan African-Cadomian-Baikalian orogeny that generated several collisional belts. We present a sequence of magmatic and tectonometamorphic events for the Cadomian belt that can be interpreted as proxies of supercontinent assembly.